End hopping based on message tampering - Kai LIN; Chun-fu JIA (Tongxin xuebao)
The main theoretical and technical problems were studied in the application of end hopping,and the idea of message tampering was proposed and the model of end hopping stack was built upon it.Three feasible implementations for the end hopping and discuss their advantages and disadvantages were respectively provided.And the experiment re-sult shows the potential application of the message tampering and the end hopping stack model in practice.